Blanka Knotková-Čapková – Aleš Karmazin a kol.: Asijské hierarchie v postkoloniálním kontextu: politické, sociální a kulturní dimenze (Czech Journal of International Relations, 2024)
This book reveals and compares the ways in which hierarchies of power are created in post-colonial societies. At the same time, it tries to deconstruct these hierarchies, ie. to reveal their initial assumptions and consequences. It thus shows that the postcolonial context is still a relevant factor that co-shapes events in Asian countries.The book specifically focuses on case studies of China, India, Japan, Central Asia and Madagascar as entities with strong Asian influences. Although the book is primarily based on Asian studies, its approach is interdisciplinary. In the analysis, it uses perspectives based on political science and international relations, anthropology, media studies or cultural and literary studies. Key categories for the analysis of hierarchies and their practices and discourses are (real and symbolic) borders, (intersubjectively shaped) identity and (political and social) norms.